Work Engagement, Physical Work Environment, Work Life Balance in Predicting Organizational Commitment and its Impact on Performance - Rahayuningsih, Lisa; Askafi, Eka; Mulyaningtiyas, Ratna Dewi (JURNAL MANAJEMEN MOTIVASI, 2025)
Human resources play a crucial role in driving the vision and mission of building an effective government organisation management. Department of Cooperatives and Micro Enterprises of Kediri Regency who are highly dedicated and have satisfactory performance. This study examines how work engagement, physical work environment, and work-life balance can predict employee performance improvement through the mediating role of organisational commitment. This type of research is associative and uses purposive sampling. This research uses the path analysis method with employee performance as the endogenous variable. The data analysis method used in this research is Partial Least Squares-Structural Equation Model (PLS-SEM) with WarpPLS software through 2nd Order stages. The results showed that work engagement, physical work environment, and work-life balance have a positive effect on organisational commitment, then the physical work environment positively affects employee performance. The role of mediation shows positively affects employee performance. The role of mediation shows that it can mediate positively affets the relationship between Work Engagement, physical work environment, and work life balance on employee performance.